Pengembangan Video Pembelajaran Making Bed untuk Mata Pelajaran Housekeeping Kelas XI di SMK Negeri 1 Singaraja - Kadek Okky Dina Donita; Ni Made Suriani; Cokorda Istri Raka Marsiti (Universitas Mathla'ul Anwar Banten, 2026)
Housekeeping instruction in vocational education requires mastery of practical skills in accordance with hotel industry Standard Operating Procedures (SOP), particularly in Making Bed competency. However, practical learning is often constrained by limited demonstration time and the lack of visual learning media that can be accessed independently by students. This study aimed to develop a Making Bed instructional video for Housekeeping subjects for eleventh-grade hospitality students at SMK Negeri 1 Singaraja and to evaluate its feasibility.This study employed a Research and Development approach using the 4D development model (Define, Design, Develop, and Disseminate). The instructional video was developed based on the duvet method in accordance with hotel industry SOP. Media feasibility was assessed through expert validation involving two subject-matter experts and two media and instructional design experts using a Likert-scale questionnaire. Data were analyzed using descriptive quantitative and qualitative methods.The results showed that the instructional video achieved a feasibility score of 100% from subject-matter experts and 99.47% from media and instructional design experts, both categorized as very feasible. These findings indicate that the developed instructional video meets content accuracy, procedural correctness, visual quality, and instructional design standards.In conclusion, the Making Bed instructional video is highly feasible and relevant as a supporting medium for Housekeeping instruction in vocational schools, particularly in enhancing students’ understanding of procedural skills aligned with hotel industry standards.